2008
DOI: 10.1094/mpmi-21-12-1539
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco mosaic virus 126-kDa Protein Increases the Susceptibility of Nicotiana tabacum to Other Viruses and Its Dosage Affects Virus-Induced Gene Silencing

Abstract: The Tobacco mosaic virus (TMV) 126-kDa protein is a suppressor of RNA silencing previously shown to delay the silencing of transgenes in Nicotiana tabacum and N. benthamiana. Here, we demonstrate that expression of a 126-kDa protein-green fluorescent protein (GFP) fusion (126-GFP) in N. tabacum increases susceptibility to a broad assortment of viruses, including Alfalfa mosaic virus, Brome mosaic virus, Tobacco rattle virus (TRV), and Potato virus X. Given its ability to enhance TRV infection in tobacco, we te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 52 publications
0
24
0
Order By: Relevance
“…To positively affect protein production, silencing suppressors may need to be specifically selected to be effective for the targeted plant species and viral vector 63 . TMV helicase has a suppressor of RNA silencing activity 64,65 . Our data confirm this observation as co-infiltration of p23 or p19 with pBID4-HAC1 resulted in no increase in GFP or a slight increase in the transient HAC1 protein production.…”
Section: Discussionmentioning
confidence: 99%
“…To positively affect protein production, silencing suppressors may need to be specifically selected to be effective for the targeted plant species and viral vector 63 . TMV helicase has a suppressor of RNA silencing activity 64,65 . Our data confirm this observation as co-infiltration of p23 or p19 with pBID4-HAC1 resulted in no increase in GFP or a slight increase in the transient HAC1 protein production.…”
Section: Discussionmentioning
confidence: 99%
“…Nicotiana tabacum and Nicotiana benthamiana were grown as described (Harries et al, 2008). Purified virus (TMV) U1 strain, (Shintaku et al, 1996)] or virus from plant extracts TVCV, CMV, and PVX (Yang et al, 2004) were used in some studies.…”
Section: Plant Materials Virus Strains and Virus Inoculationsmentioning
confidence: 99%
“…It was recently shown that the tobacco mosaic virus 126-kD protein suppressor expressed as a transgene in N. benthamiana allowed a stronger silencing phenotype when expressed at a low level versus either a high level or in its absence (Harries et al, 2008). It was hypothesized that the suppressor expressed at a low level allowed a higher level of the virally encoded host gene transcript to be targeted by the silencing system.…”
Section: Resources Limitations and Future Developmentmentioning
confidence: 99%